PROXIMATE COMPOSITION, MINERALS CONTENT AND FUNCTIONAL PROPERTIES OF CRICKET (ACHETA spp.) - Abulude, F O (Biological Sciences - PJSIR, 2004)
Proximate composition, minerals content and functional properties of field cricket (Acheta spp) were analyzed using standard methods. The result of the proximate content (%) was as follows: crude protein (39.9±0.40), crude fibre (5.2±0.1), carbohydrate by difference (39.9± 0.1) and energy (46.7Kcal). The predominant mineral was potassium and zinc was the least. The functional properties (%) ranged as follows: Water absorption capacity (100), oil absorption capacity (205.6), oil emulsion capacity (75), foaming capacity (28), least gelation capacity (10). Foaming stability was low and collapsed after 240 min. Emulsion stability was high. The result suggests that cricket is a good food formulation medium.